Fish communities in shallow coastal waters - a study of effects of season and bottom substrate - Sørensen, Ole Johannes Ringnander (UiT The Arctic University of Norway, 2019)
Fish communities in the outer part of Malangen fjord, Troms county were studied to identify seasonal and spatial variation. The fish species compositions differed between seasons and at the four different locations. Cod (Gadus morhua L.) dominated the trammel net catches at all months except in March, in which plaice and other flatfishes were the most numerous. Species richness and diversity were significantly positively correlated with substrate evenness, and the species richness was highest in October and lowest in March. Cod displayed a higher length at age compared with fjord populations, but lower maximum length (L∞). Plaice (Pleuronectes platessa L.) had a low annual mortality rate, and the von Bertalanffy growth coefficient (K) were higher than North Sea plaice populations. Only immature halibut (Hippoglossus hippoglossus L.) were observed, and the three locations where halibut were present are suggested to be nursery grounds for this species. Most of the flatfishes were positively associated with sand and pebble habitats whereas cod were significantly negatively correlated with sand coverage but positively correlated with high algae coverage. The present study highlights the importance of including shallow water studies for both coastal and fisheries management.